Meanings of work for manicurists and hairdressers: employees and pejotizados - Souza,Mariana Machado (2021)
Abstract The research aimed to identify the differentiation of meanings of work among beauty salon workers, considering the work contracts and the functions performed (hairdressers and manicurists), in a context of pejotização and functions’ internal hierarchy. We applied questionnaires to 171 manicurists and hairdressers with the following types of links: employee, informal, MEI pejotizado and MEI não pejotizado. The results indicated that employees perceive with greater intensity the work as a responsibility and as a way of being socially included, and more proportionality in social and financial retribution. They also indicated that manicurists experience with more intensity the characteristics of brutalization, discrimination and demand.